Constructive Communication Patterns and Associated Factors Among Male Couples. Issue 2 (3rd April 2018) - Mitchell, Jason W.; Gamarel, Kristi E.
ABSTRACT: Constructive communication is an important correlate to examine for sexual health promotion and HIV prevention among male couples. However, few studies have examined the effect of different relationship dynamics on both partners' perceptions of constructive communication. Using dyadic data collected from 361 male couples, the present authors explore which relationship dynamics were associated with constructive communication patterns. The results highlight the relevance of investment in a sexual agreement and trust within the relationship in perceptions of constructive communication. These findings may be particularly useful to guide the development of future dyadic-focused sexual health and HIV preventive interventions for male couples.